Clinical significance of ureteric 'skip lesions' at the time of radical cystectomy: the M.D. Anderson experience and literature review. (May 2014) - Hoang, Anthony N.; Agarwal, Piyush K.; Walton‐Diaz, Annerleim; Wood, Christopher G.; Metwalli, Adam R.; Kassouf, Wassim; Brown, Gordon A.; Black, Peter C.; Urbauer, Diana L.; Grossman, H. Barton; Dinney, Colin P.N.; Kamat, Ashish M.
Abstract : Objective: To assess the incidence and clinical significance of 'skip lesions' that are present in proximal but not in distal ureteric sections, which are occasionally found during the pathological examination of ureteric margins during radical cystectomy (RC). Patients and Methods: We identified 660 patients who underwent a RC and had at least two permanent margins for a given ureter. In all, 1173 ureters were analysed and classified as follows: 'normal' (no tumour, reactive atypia, mild or moderate dysplasia) or 'abnormal' (severe dysplasia, carcinoma in situ (CIS), or tumour). Transitions from 'normal' distal pathology to 'abnormal' on proximal section(s) determined frequency of skip lesions. Fisher's exact test and the log‐rank test were used to study correlations. Results: Ureteric skip lesions were found in 4.8% patients (2.9% ureters). Pathology of skip lesions was CIS in 55.9%, transitional cell carcinoma in 23.5% and severe dysplasia in 20.6%. Skip lesions were associated with lymphovascular invasion (34.4% vs 13.7%, P = 0.004) and advanced pT stage ( P = 0.007). On multivariate analysis, skip lesions correlated with lower median overall survival (OS) (inestimable vs 8.2 years, P = 0.014) in patients with pT0 or pTa disease and a trend towards lower OS (2.7 vs 8.8 years, P = 0.066) in pTis disease. Concordance between frozen distal margin and permanent proximal margin varied; sensitivity was 80% in those without and 20% in those with skip lesions. Conclusions: The presence of a ureteric skip lesion may be associated with lower survival in patients with pT0, pTa or pTis urothelial carcinoma. Thus, while uncommon, ureteric skip lesions should be reported in pathological findings.